GDP versus ESHAP Regimen in Relapsed and/or Refractory Hodgkin lymphoma: A Comparison Study - Mani Ramzi; Aliraza Rezvani; Mehdi Dehghani (International Journal of Hematology-Oncology and Stem Cell Research, 2015)
Background: Despite multiple published studies reporting result of salvage regimens for relapsed and refractory Hodgkin’s lymphoma, there are no comparisons of different combinations. Patients and methods: A Total of 44 patients identified with refractory or relapsed Hodgkin’s Lymphoma were considered eligible for this study. The Patients were randomly divided into two groups of 22, one of which were treated with GDP regimen (gemcitabine, dexamethasone and cisplatin) and the other with EHSAP regimen (etoposide, methyl prednisolone, cisplatin and cytarabine) in a prospective manner. The results of each group were compared. Results: There were 27.3% complete response, 31.8% more than 50% response, and 40.9% no response with GDP. ESHAP results were 29.5%, 24% and 45.5%, respectively. Conclusion: There is no significant difference in response rate between GDP and ESHAP regimens as salvage chemotherapy in refractory or relapsed Hodgkin’s Lymphoma.